Adipose tissue: from amorphous filler to metabolic mastermind. (12th April 2021) - Corvera, Silvia
Abstract : Adipose tissue plays a central role in the control of systemic glucose homeostasis through two major mechanisms: fat storage and secretion of specific cytokines known as adipokines. Fat storage in adipose tissue is critically important, as it prevents lipid deposition in liver and muscle, which in turn results in insulin resistance and increased risk of type 2 diabetes. Secretion of adipokines, such as leptin, protects from fuel depletion through appetite control, and other adipokines control fuel distribution and utilization. Fat storage capacity of adipose tissue increases through two mechanisms, adipocyte hypertrophy and adipocyte hyperplasia. Adipose tissue depots expand differently in diverse individuals and confer varying degrees of metabolic disease risk. There are multiple adipocyte subtypes that together mediate the functions of adipose tissue. They do so through specialized functions such as thermogenesis, which burns fuel to maintain core temperature, and through selective secretion of different adipokines. Much progress has been made in understanding the mechanisms by which adipose tissue controls systemic metabolism, increasing our hope of developing new, effective therapies for metabolic diseases.